Add these tools to your ASD toolbox. Issue 4 (November 2015) - Hope, Joan
<x xml:space="preserve">Abstract</x> ST. PAUL, MINN. — Chances are you're seeing a lot more students with autism spectrum disorder on your campus than you did in years past. Among the age group of students entering college now, the prevalence of individuals with ASD is about one in 110 people, said Michelle Rigler, director of the Disability Resource Center and the MoSAIC program at the University of Tennessee‐Chattanooga. Building a toolbox can help you serve students with ASD from their adjustment to college to their successful job hunt.